First Early Pliocene micromammal faunas from Venta del Moro (Cabriel Basin, Spain): new data on the Messinian dispersal of Debruijnimys - Mansino, Samuel; Ruiz-Sánchez, Francisco Javier; de Luque, Luis; Montoya, Plinio; Gibert, Luis; Morales, Jorge; Abellá, Juan; Scott, Gary R.; Crespo, V.D. (Journal of Iberian Geology, 2015)
Based on the study of the micromammal assemblages from the localities of La Bullana 2B and La Bullana 3 (Valencia, E Spain) we propose an Early Pliocene age (MN14) for both sites. The presence of a form related to the gerbillid Debruijnimys julii in La Bullana 2B allows extending the stratigraphical range of this taxon to the MN14 zone, opening new questions about the phylogenetic relationship between Debruijnimys species from the Early and Late Pliocene of the Iberian Peninsula. Furthermore, preliminary paleomagnetic data indicate an age of 4.816 Ma for La Bullana 2B, and between 4.896 and 4.997 Ma for La Bullana 3.